1997
DOI: 10.1016/s0022-5347(01)64127-2
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Alterations of the Tunica Albuginea in Impotence

Abstract: An alteration in the distribution and structure of the various collagen types and lectins in the tunica albuginea of impotent patients has been shown that may interfere with normal function and lead to impotence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…In the tunica albuginea, the collagen bundles were described as disposed in an outer longitudinal and an inner circular layer [9,18,21,22]. This arrangement was also observed in the present work in fetuses at 28 WPC.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In the tunica albuginea, the collagen bundles were described as disposed in an outer longitudinal and an inner circular layer [9,18,21,22]. This arrangement was also observed in the present work in fetuses at 28 WPC.…”
Section: Discussionsupporting
confidence: 87%
“…Different opinions exist concerning the role of the collagen fibers in the tunica albuginea. Possibly, the collagen bundles enable the tunica albuginea to withstand greater corporal pressure by preserving the normal corporal expansion and the veno-occlusive function during erection [9,10,21,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histological studies have shown an association between vasculogenic ED and ECM deposition [132][133][134][135][136][137][138][139]. The severity of ED has been correlated with a reduced smooth muscle/ECM ratio [1,[135][136][137].…”
Section: Effects Of Androgens On Corpus Cavernosum Extracellular Matrmentioning
confidence: 99%